2019
DOI: 10.1152/physiol.00009.2019
|View full text |Cite
|
Sign up to set email alerts
|

Supraventricular Arrhythmias in Athletes: Basic Mechanisms and New Directions

Abstract: Athletes are prone to supraventricular rhythm disturbances including sinus bradycardia, heart block, and atrial fibrillation. Mechanistically, this is attributed to high vagal tone and cardiac electrical and structural remodeling. Here, we consider the supporting evidence for these three pro-arrhythmic mechanisms in athletic human cohorts and animal models, featuring current controversies, emerging data, and future directions of relevance to the translational research agenda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 132 publications
0
11
0
Order By: Relevance
“…These findings are contested by studies in rodents (e.g., Aschar-Sobbi et al, 2015) and dogs (Billman et al, 2015) where training induced intrinsic slowing was not observed and instead a role for high vagal tone was determined. The evidence for intrinsic vs. autonomic mechanisms in underlying training-induced sinus bradycardia has been extensively reviewed by our group (Boyett et al, 2013(Boyett et al, , 2017D'Souza et al, 2015D'Souza et al, , 2019 and we posit that non-uniform methodology (species, drug doses, and training modalities) contribute to the reported discrepancies. Furthermore, based on our present results we advance that both vagally mediated and intrinsic SAN remodeling-based mechanisms of the HR adaptation to training may be reconciled: we speculate that (currently uncharacterized) training-induced alterations in sympathetic and/or parasympathetic input may trigger transcriptional remodeling of SAN ion channels, leading to a decrease in intrinsic automaticity as observed.…”
Section: Impact Of the Studymentioning
confidence: 91%
“…These findings are contested by studies in rodents (e.g., Aschar-Sobbi et al, 2015) and dogs (Billman et al, 2015) where training induced intrinsic slowing was not observed and instead a role for high vagal tone was determined. The evidence for intrinsic vs. autonomic mechanisms in underlying training-induced sinus bradycardia has been extensively reviewed by our group (Boyett et al, 2013(Boyett et al, , 2017D'Souza et al, 2015D'Souza et al, , 2019 and we posit that non-uniform methodology (species, drug doses, and training modalities) contribute to the reported discrepancies. Furthermore, based on our present results we advance that both vagally mediated and intrinsic SAN remodeling-based mechanisms of the HR adaptation to training may be reconciled: we speculate that (currently uncharacterized) training-induced alterations in sympathetic and/or parasympathetic input may trigger transcriptional remodeling of SAN ion channels, leading to a decrease in intrinsic automaticity as observed.…”
Section: Impact Of the Studymentioning
confidence: 91%
“…Supraventricular arrhythmia number post high-volume endurance exercise was also related to baseline supraventricular number. This result is not unexpected, considering that high volume endurance exercise is accepted as a factor contributing to the development of supraventricular arrhythmias ( D’Souza et al, 2019 ), including bradyarrhythmia, atrioventricular block ( Baldesberger et al, 2008 ) and atrial fibrillation ( Andersen et al, 2013 ; Myrstad et al, 2014 ). Further, supraventricular arrhythmias can have serious quality of life and sport participation consequences in athletes ( D’Souza et al, 2019 ), although in the general population it has been suggested that they are common and rarely life threatening ( Blomstrom-Lundqvist et al, 2003 ).…”
Section: Discussionmentioning
confidence: 79%
“…Physiologically, HRA was related to sinus node innervated by autonomic nervous system, which modulated heart rhythm through neurotransmitter release [26]. This was the reason that the disturbed HRA could provide diagnostic evidences for many pathologies [7,8,27].…”
Section: Resultsmentioning
confidence: 99%